In-line Measurement Techniques of Resin-based Insulation Processes for Wireless Power Transfer Systems - Kneidl, Maximilian; Benke, Daniel; Masuch, Michael; Kühl, Alexander; Franke, Jörg (2021 IEEE Conference on Electrical Insulation and Dielectric Phenomena (CEIDP), 2021)
The increasing demand for electric mobility is continuously generating innovations in the development and production of electrical machines such as wireless power transfer (WPT) systems. Therefore, new insulation resins with different filler types are investigated in detail to prevent electrical breakdowns and to increase the thermal conductivity of the whole insulation system. In contrast to the development and optimization of new materials, the application technology, process control and testing still remains largely unchanged. As a result, the transfer of the optimized material properties of new insulation resins to the specific component properties is restricted. In the worst case, this leads to an inappropriate processability of the resin and subsequently to the failure of the electrical machine. Furthermore, end-of-line tests only allow a qualification of the final insulation system after impregnation and curing. Thus, defective components can only be identified and discarded or repaired at the end of the process chain, which causes additional costs in production. The aim presented in this work is to identify and measure the dielectric properties of the insulation material along the encapsulation process of a coil structure for WPT systems, to derive information about the overall quality of the insulation system. Therefore, a test setup for qualifying the insulation system capability during the encapsulation process will be elaborated. The results of the in-line measurements are then validated with partial discharge measurements and micrographs of the conductor structur